(untitled) (Public Sector Economics - submission site, 2021)
Poland’s marketable government debt has grown from essentially zero in the early 1990s to USD 180 bn by 2019, with a wide range of maturities and security types. The aim of the article is to describe the long-term trends in the Polish sovereign local currency debt. Changes in its composition, maturity profile and ownership structure are analysed. The Ministry of Finance’s databases on bond transactions and secondary market activity are used. Since early 2000s the market has become less fragmented and the ownership structure has shifted considerably in reaction to global and national factors. Debt management strategy has stabilized the market and reduced frictions. Countries developing their local currency bond markets should be encouraged to avoid market fragmentation and concentrate on selected benchmark issues. Creating a functioning local currency bond market is essential in avoiding the so called “original sin”, but must be part of a broader institutional push.